An ethnogeography of the maleku indigenous peoples in northern Costa Rica - Castillo Vásquez, Roberto 1962 - (Kansas, 2004)
Tesis (doctor of philosophy)--Department of Geography and the Faculty of the Graduate School of the University of Kansas, 2004.
Tesis (doctorado) -- Department of Geography and the Faculty of the Graduate School of the University of Kansas, 2004
Keywords: HISTORIA; INDIOS COSTARRICENSES; VIDA SOCIAL Y COSTUMBRES; GUATUSO (PUEBLO INDIGENA COSTARRICENSE)